2009
DOI: 10.1073/pnas.0903458106
|View full text |Cite
|
Sign up to set email alerts
|

Renal fibrosis is attenuated by targeted disruption of K Ca 3.1 potassium channels

Abstract: Proliferation of interstitial fibroblasts is a hallmark of progressive renal fibrosis commonly resulting in chronic kidney failure. The intermediate-conductance Ca 2+ -activated K + channel (K Ca 3.1) has been proposed to promote mitogenesis in several cell types and contribute to disease states characterized by excessive proliferation. Here, we hypothesized that K Ca 3.1 activity is pivotal for renal fibroblast pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
137
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(160 citation statements)
references
References 51 publications
10
137
1
Order By: Relevance
“…A few recent papers show increased cell proliferation in TIF models and indicate that limiting cell proliferation could improve fibrosis development (45)(46)(47). Therefore, it might be interesting to speculate the role of cell proliferation in humans with TIF and in murine TIF models.…”
Section: Discussionmentioning
confidence: 99%
“…A few recent papers show increased cell proliferation in TIF models and indicate that limiting cell proliferation could improve fibrosis development (45)(46)(47). Therefore, it might be interesting to speculate the role of cell proliferation in humans with TIF and in murine TIF models.…”
Section: Discussionmentioning
confidence: 99%
“…3). Recent studies have shown that K Ca such as K Ca 3.1 and small-conductance Ca 2ϩ -activated K ϩ channel (SK Ca 2/ K Ca 2.2) participate in the modulation of cell proliferation in several types of cells and that their pharmacological blockade and down-regulation inhibit cell proliferation by G 0 /G 1 arrest (Morimoto et al, 2007;Wang et al, 2007;Grgic et al, 2009). This suggests that the inhibitory effects of TRAM-34 on in vivo cell proliferation in the implanted UGS of stromal BPH model rats may be responsible for the termination of cell cycle progression from G 0 /G 1 by TRAM-34 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…40 All of these factors have been implicated in the pathogenesis or treatment of various conditions resulting in renal fibrosis. [41][42][43][44] Significantly, IHG-1 expression has been shown to be increased in both DN and an experimental model of renal fibrosis (UUO) in which TIF is well modeled. 4,45 Oxidative stress is a key early event in both of these conditions.…”
Section: Discussionmentioning
confidence: 99%